The Relationship Between COVID-19 Pandemic and Nutrition in the Light of Health Literacy (Turkey Health Literacy Journal, 2020)
Coronavirus disease 2019 (COVID-19) has been declared a global pandemic by the World Health Organization. The rapid transformation of the COVID-19 disease into a pandemic has forced people to learn about the new virus and change their practices and behaviors rapidly. In the society, especially during this period when staying at home was recommended, curiosity about how best to support the immune system to prevent this disease has increased. The optimum immune response required to keep infection at bay depends on diet and nutrition. Health literacy is important in every period, especially in epidemic periods, in terms of preventing diseases, and promoting and improving health and staying healthy. The low health literacy in our society and the rapidly advancing covid-19 pandemic have caused the spread of false information. The society does not know how the decisions taken in line with false information will affect their health. In this review, the effects of nutrition and diet on the immune system during the COVID-19 pandemic process were examined by examining scientific studies. However, as seen in the literature review on this subject, the studies conducted are promising but there is knowledge gap.